Establishing green practice constructs among secondary school student in Malaysia: confirmatory factor analysis approach (CFA). - Hanifah Mahat (Tanjong Malim, 2019)
Establishing green practice constructs among secondary school student in Malaysia: confirmatory factor analysis approach (CFA). by Hanifah Mahat